2019
DOI: 10.3389/fnagi.2019.00259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Sex on Subcortical Volumes

Abstract: PurposeIn an increasingly aging society, it is of great importance to consider trajectories of subcortical volumes at different ages for understanding biological markers of aging. Thus, we investigated sex, age, and their interactions on subcortical volumes, including the basal ganglia (caudate, putamen, accumbens, and pallidum), thalamus, hippocampus, and amygdala.MethodsWe analyzed the adult lifespan trajectory of subcortical volumes and asymmetries in 563 healthy subjects aged from 19 to 86 using magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 77 publications
9
38
2
Order By: Relevance
“…After such adjustment, this region becomes statistically insignificant (Table 4, Figure 6). However, there are contradictory reports for this structureno significant sex-related difference was found by Ritchie et al (2018), while Yanpei Wang et al observed more rapid decrease of the volume of right thalamus in the males than in the females (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…After such adjustment, this region becomes statistically insignificant (Table 4, Figure 6). However, there are contradictory reports for this structureno significant sex-related difference was found by Ritchie et al (2018), while Yanpei Wang et al observed more rapid decrease of the volume of right thalamus in the males than in the females (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the standardized regression coefficients (β) and the significance of the regressor effects (p-values) were calculated to characterize age-related dimorphism and in the subsequent models, to adjust the TBV and ICV factors in this description. The p-values less than 0.05-a predetermined significance level-were accepted as indicating that the observed result would be highly unlikely under the null hypothesis (Király et al, 2016;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[111][112][113][114][115][116] Although the question whether there is significant adult neurogenesis remains a matter of controversy, 117 this specific region of the brain has been suggested as having an annual turnover of neurons of almost 2%. 118 Hippocampal gray matter volume alterations have been demonstrated in connection with normal physiological variability like exercise, 119 the menstrual cycle, 120 and aging 121 as well as in pathological conditions like Alzheimer's disease, 122 mild cognitive impairment, 123 post-traumatic stress disorder, 124 major depressive disorder, 125 126 Parkinson's disease, 127 and Cushing's syndrome, [112][113][114][115][116] all of which are illnesses with mental symptoms. These wideranging results are not easy to interpret.…”
mentioning
confidence: 99%
“…Such non-specificity may be at least partly addressed by investigating diseases across the lifespan, since some of brain changes reported in psychiatric disorders also occur in aging or development in healthy subjects, e.g. volumetric changes in subcortical structures in schizophrenia (Okada et al, 2016; and in healthy aging (O'Shea et al, 2016;Wang et al, 2019). We initially coordinated with 13 sites to explore various psychiatric and neurological disorders throughout the lifespan and to make use of a powerful harmonization method.…”
Section: Discussionmentioning
confidence: 99%